2014
DOI: 10.1371/journal.pone.0097480
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Climate Change and the Dietary Choices of Young Adults in Finland: A Population-Based Cross-Sectional Study

Abstract: Climate change is a major public health threat that is exacerbated by food production. Food items differ substantially in the amount of greenhouse gases their production generates and therefore individuals, if willing, can mitigate climate change through dietary choices. We conducted a population-based cross-sectional study to assess if the understanding of climate change, concern over climate change or socio-economic characteristics are reflected in the frequencies of climate-friendly food choices. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 33 publications
(69 reference statements)
5
31
3
Order By: Relevance
“…For example, public awareness of heat waves influences attitudes towards the influences of heat waves on the society and the reframing and communication strategies [7]. Increasing climate change awareness brings greater use of eco-friendly food on the basis of reducing GHG emissions and mitigating climate change [2]. Public opinion on climate change concerns is also related to environmental attitudes and the adoption of energy efficient behavior to reduce emissions [4].…”
Section: Climate Change Awareness Attitude and Behavioral Intentionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, public awareness of heat waves influences attitudes towards the influences of heat waves on the society and the reframing and communication strategies [7]. Increasing climate change awareness brings greater use of eco-friendly food on the basis of reducing GHG emissions and mitigating climate change [2]. Public opinion on climate change concerns is also related to environmental attitudes and the adoption of energy efficient behavior to reduce emissions [4].…”
Section: Climate Change Awareness Attitude and Behavioral Intentionmentioning
confidence: 99%
“…The constructs represented climate change awareness, climate change mitigation pursuing actions, anticipated pride, anticipated guilt, subjective norm, attitude, and perceived behavioral control, and intention. Six items addressing the construct of climate change awareness were generated from prior research [2,8,33]. Six items to assess the construct of climate change mitigation pursuing actions were adapted from the literature [5,10,35].…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not study intentions but assessed the actual food intake frequencies. Therefore our study adds to the previous knowledge: the high concern about climate change might actually concretize the intentions to make dietary adjustments" (Korkala, Hugg, & Jaakkola, 2014).…”
Section: Strengths and Weaknesses In Relation To Other Studies Discumentioning
confidence: 69%
“…In addition, females polluted more than males. This result is quite unexpected, since studies have found that climate change often burdens women more than men, that marginalization of women makes them more vulnerable to climate change impacts than men, and that women are generally more concerned about climate change than men (Korkala, Hugg, & Jaakkola, 2014;McCright, 2010;Habtezion, 2012;Olsson et al, 2014). 10 Furthermore, the subjects who were of the opinion that it is unfair for Africa to reduce emissions polluted more (kept 2.7 more red cards) than their counterparts who thought it was fair.…”
Section: Resultsmentioning
confidence: 99%